The Effect of Green Human Resource Management on Performance with Green Lifestyle Moderation and Perceived Organizational Support - Nathania, Nathania; Sandroto, Christine Winstinindah (International Business Management - Universitas Ciputra, 2022)
The purpose of this study was to analyze the effect of green hu- man resources management on employee performance with a green lifestyle and perceived organizational support moderation on employees in Jakarta and Tangerang companies. This study uses a convenience sampling method with a sample of 228 respondents in Jakarta and Tangerang. The analytical method used is moderated multiple regression analysis, which is processed through SPSS version 25. Questionnaires that are applied as research in- struments are green human resource management, green lifestyle, perceived organizational support, and employee performance. The results of this study indicate that green HRM has a significant effect on employee performance. Perceived organizational support and green lifestyle are proven to moder- ate the influence of green HRM on employee performance. Keywords: green human resource management, green lifestyle, perceived organizational support, and employee performance